RANCANG BANGUN SISTEM KEAMANAN PADA KOTAK PENYIMPANAN UANG (MONEYBOX PLUS) BERBASIS MIKROKONTROLER ARDUINO - Annabawi, Achmad; Pratama, Firman Hadi Sukma (Informatics Department-Universitas Wijaya Kusuma Surabaya, 2024)
Even though many have provided practical means of saving money, some people still prefer to keep their money privately at home, because not all banks have many branches or cash deposit machines, and there is an imbalance in the distance traveled. far to the cash deposit tool. The design of the MoneyBox Plus tool with a security system that uses a magnetic lock and is equipped with an alarm and the use of a security code (password) as access to MoneyBox Plus. The method used in data collection and analysis as well as the steps to be carried out in this study is the prototype method. In this study, the Fisher Yates Algorithm is implemented using the function contained in the Arduino program, namely random(). The random() function is a function that is used to generate random values. The aim of this research is that the security system can be monitored better and ensure that only entitled people have access, and can anticipate saving money.